Peran Media Sosial Dalam Meningkatkan Potensi UMKM F&B dan Handcraft di Kelurahan Gebang Putih - Reksa Daninzia Ramadhan; Wahyu Fahrul Ridho (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research explores the role of social media in enhancing the potential of micro, small, and medium-sized enterprises (UMKM) in the Food & Beverages (F&B) and handicraft sectors in Kelurahan Gebang Putih. Despite offering promising opportunities for UMKM development, many businesses in the area still face marketing challenges. The study employs quantitative and observational methods, along with counseling and mentoring stages, to investigate the current marketing practices and identify potential strategies. The findings reveal that while some UMKM have experienced rapid growth and increased production, they have yet to fully utilize social media for promotional purposes. Recommendations include intensifying digital marketing knowledge, adopting innovative technologies, and establishing partnerships with educational institutions. By optimizing social media, UMKM can elevate their product marketing, increase visibility, and foster business growth, ultimately contributing to the local and national economy.